Effect of interlaminar cation type on the pillaring capacity of the synthetic mica Na-2-Mica and the in – situ formation to MnS Nanoclusters (2018)
In this work the Na-2-mica was synthesized by the sol-gel method and the effect of the cation exchange with lithium and hexadecylammonium, prior to the pillaring process with the Al Keggin’s polycation, was studied. The study was done by varying the density of pillars (10, 20 and 30 meq.Al3+ per gram of mica). The cation exchange with hexadecylammonium cations ensured the expansion of the interlayer; however, the study revealed that after the heat treatment in the pillaring process, the interlayer is not kept expanded, due to the high layer charge and the strongly acidic sites of mica. Most materials obtained formed particles of alumina (Al2O3) in the interlayer spacing, where the aluminum content and % CC increased as higher pillar density is provided. In addition, the formation of MnS nanoclusters in the pillared Al-2-mica was studied and the results indicated a limited growth of the nanoclusters respect to the Al content, due to amount interlayer alumina phase prevented proper diffusion of H2S(g) so they were deposited on the surface of the solid. All materials were mainly characterized by XRD, elemental analysis, analysis of the cation exchange capacity CEC and percentage of compensated charge -% CC.